Design and Implementation of Bekantan Educational Game (BEG) as a Banjar Language Learning Media - Syahidi, Aulia Akhrian; Supianto, Ahmad Afif; Tolle, Herman (International Journal of Interactive Mobile Technologies (iJIM), 2019)
The lack of recognition of the current Banjar language is one of the causes of knowledge and the introduction of children about the reduced Banjar language. In an attempt to recognize, introduce, and improve the re-knowledge of the Banjar language is to recommend the design and implementation of an educational game application called Bekantan Educational Game (BEG) containing material content and quizzes. Before this game application is used, it must be tested first. Test method used is black box testing, to test the functionality of game applications. Other tests are also conducted to obtain information about the material access frequency and reset quizzes by players. The result of black box testing is all the functionality in the BEG application in accordance with what is expected. The result of the frequency testing accessing the menu on BEG of Material Section is Wadai Banjar 2 Menu with 59 times, and the frequency reset on BEG of Quiz Section is a type of Drag and Drop quiz with 21 times and generate feedback from quiz in the form of final value with average 89.17%.